Kanjeng Raden Tumenggung (KRT) Sumadiningrat bukan Habib Hasan bin Thoha bin Yahya: Analisis Kritis di Balik Kesalahpahaman Sejarah - M. Yaser Arafat (Warisan: Journal of History and Cultural Heritage, 2023)
This article critically examines the claim made by Majelis Taklim Darul Hasyimi that KRT Sumadiningrat, a Yogyakarta Palace figure who died during the Geger Sepehi incident in 1812, is Habib Hasan bin Thoha Bin Yahya. Despite historical primary sources not supporting this assertion, the claim persists. Utilizing primary sources from historical documents, chronicles, and national booklets at the Yogyakarta Palace, the article thoroughly investigates the identities of both KRT Sumadiningrat and Habib Hasan bin Thoha Bin Yahya. Analyzing crucial human aspects such as birth, parentage, marriage, and death, the research concludes that KRT Sumadiningrat is not Habib Hasan bin Thoha Bin Yahya, and vice versa. The article argues that the claim represents a distortion of history orchestrated by certain religious groups in society. In the context of Indonesia's post-212 Movement era characterized by heightened religious sentiments, this distortion may gain more credibility than historical accuracy.